Relevance of DNA repair genes polymorphisms in an individual risk of multiple head and neck cancer. A preliminary report - Szyfter, Krzysztof; Kujawski, Maciej; Gajęcka, Marzena; Rydzanicz, Małgorzata; Wierzbicka, Małgorzata (Contemporary Oncology/Współczesna Onkologia, 2003)
DNA repair plays a critical role in maintaining the genome stability. Polymorphisms of DNA repair genes may be associated with differences in the repair of carcinogen-induced DNA damage, and may influence an individual risk of head and neck cancer. We examined the relevance of polymorphisms of three DNA repair genes: XRCC1 (G28152A and C26304T), XRCC3 (C18067T), XPD (A35931C and C22541A) in relation to the risk of multiple head and neck tumors. The study groups were: subjects with primary laryngeal tumor (n= 167), subjects with multiple primary tumors of head and neck (n=63) and healthy controls (n=118). Genotypes were identified using the PCR-RFLP technique. The statistic analysis was performed to calculate odds ratio (ORs), 95% confidence intervals (CIs) and P values. The XPD 35931AC and 22541CA genotype variants were more frequent in multiple HNSSC (53.2% and 59.7%, respectively) than in patients with a single cancer (41.9% and 45.8%, respectively) and controls (48.3% and 54.2%, respectively), but did not reach the level of statistic significance. The statistically significant difference of frequency of genotypes AC and CA was found in controls compared with primary cancer subject [OR=0.49; 95% CI= 0.29-0.85; P=0.010] and primary cancer subjects compared with multiple cancer patients [OR=2.30; 95% CI=1.21-4.37; P=0.009]. Due to relatively small number of subjects in the subgroups the findings need to be verified by further studies in larger groups; gene-gene interaction should be also taken into account.